Application of Restorative Justice in Domestic Violence by Women's and Children Units of Barelang Resort Police - Retno Ariani (Universitas Airlangga, 2020)
Domestic violence is any act against a person especially a woman, resulting misery or physical, sexual, psychological and child neglect or suffering. Domestic violence is a hidden crime because there are many victims, but few report incidents. The punishment for the perpetrators must be considered by the principle of expediency and justice. If the concept of restorative justice is done correctly, it can create justice and balance between the perpetrators of crime and the victims. The research method used in this paper is normative legal research, literature studies and case studies. The application of the concept of restorative justice carried out by women's and children protection units of the Barelang Resort Police is making collaboration with CJS and related agencies such as social services in handling cases of violence. The result is that the handling of domestic violence cases in the Barelang Resort Police can be more focused and resolved.